Agronomic performances of blast infected rice varieties under silicon application - Esa, Nurulnahar (2020)
Rice blast (Pyricularia oryzae Carava [teleomorph: Magnaporthe grisea (Herbert) Barr]) is considered a major rice disease because of its wide distribution and extent of destruction under favourable conditions. The economical approach for controlling the blast disease is the use of resistant varieties. However, chemical control is the most widely used. Resistant cultivars have a limited effect due to the breakdown of resistance genes with increasing blast pathotypes overcoming rice resistance. While, continuous use of chemical fungicides also leads to the reappearance of resistant races of the pathogen. Silicon (Si) has been reported to increase the growth and yield of a broad range of crops and beneficial in controlling diseases caused by both fungi and bacteria in different plant species. To manage rice blast in an effective and sustainable way, all crop protection practices in future should consider new approaches such as using Si fertilizer. The objective of this study was to investigate the effect of Si on panicle blast disease and grain yield of resistant and susceptible rice varieties. Experiments were conducted under controlled and under field conditions on two rice variety, MARDI Siraj 297 (resistant) and MR 263 (susceptible). Results showed that under controlled conditions application of Si to rice plants decreased panicle blast severity as the Si rates increased from 0 kg/ha to 400 kg/ha as well as increased Si deposition in rice panicles. This strongly supports the hypothesis that application of Si to rice plant improved the resistance against panicle blast. The increase in Si density in rice panicle thus prevent against appressoria penetration of the blast fungus into the panicle. Results also showed that, non-structural carbohydrate decreased at 200 kg Si/ha in rice panicles that lead to decline in grain yield. Panicle blast disease was found under natural field conditions. The disease occurred in low levels incidence thus the effect of Si had no influence. The application of Si at reproductive stage (panicle initiation) improved production of grain, with concomitant increase in nitrogen uptake. Higher grain yield was associated with increased number of panicles per square meter and number of spikelet per square meter. The findings in this study indicated that panicle rice blast disease can be managed with 245 kg Si/ha. This could reduce 24% of panicle blast severity and consequently increased the grain yield by 11%. Scientific evidence in the present study supports the beneficial use of Si as a fertilizer in rice cultivation in Malaysia.